The application of regression analysis on users tolerance to prolonged waiting time: the case of KTM Komuter services of Malaysia - Bachok, Syahriah; Mohamed Osman, Mariana; Khalid, Ummi Aqilah; Zainaldin, Mohd Faisal (WIT Pres, 2013)
Public transport routes and services are the vital movement agents in urban areas. Amongst issues of public transport performances are waiting time and transfer penalties incurred during multi-modal journey undertakings. This study has applied regression analysis on prolonged waiting time in order to quantify passengers’ tolerance to inconsistencies in train departure and arrival times. Some 1000 users of KTM Komuter services, in Kuala Lumpur, Malaysia have participated in this study. The regression analysis model which is being developed shows that high tolerance to waiting time have been persistent among many commuters of the rail services. Several independent variables including socio-demographic and rail services characteristics have been found to have influenced this high level of tolerance. Other models have also been developed for variation to tolerance to punctuality (time arriving), modified ticketing systems, delays time, changing frequency, increased safety eleme n! ts, and convenience levels. The regression analysis results have shown that if these inefficiencies and inconsistencies are not addressed in a timely and systematic manner, public transport services will experience more dwindling numbers of passengers in the near future. The models developed, are deemed to be useful for the services operators and regulators since they are planning and developing various systems improvements in the coming years to encourage mode switching behaviours from private vehicles to public transport use.